Voice over ZigBee mesh network (Voize) - Nacion, John Carlo N.; Dizon, Jefferson C.; del Mundo, Vincent Cris M. (2009)
ZigBee is a low cost, wireless network protocol that can be used in wireless sensor networks. ZigBee networks are designed to have low power consumption, low data rate, and can be used in complex applications. This project provides a design methodology for a wireless mesh network that is an IEEE 802.15.4 and ZigBee compliant. Each node in the network is composed of an EZZBM05 ZigBee module and EZZBDU01 Development Board kit. Each node in the network can transmit and receive hex files to and from the coordinator or base station. A mother board was fabricated to hold an audio reference board from Jennic and a ZigBee module. The audio device and the ZigBee module will be integrated to be able to transmit live audio files through the network.
Thesis (B.S., EEE)--University of the Philippines, Diliman.
Keywords: Wireless LANs -- Standards; Wireless communication systems; Zigbee; Voice over Zigbee